Creating of Something from Nothing. Methodic. (Applying the Principles of Chaos and Complex Systems in a Learning Environment) - Vasileva, Evgenia (Research Papers, 2017)
The analysis focuses on the field between biology, physics, information technology and society, where we are researching the so-called “complex (self-sustaining, live) systems”. The system that we are interested in is the education in political sciences, and the “nothing” is a form of complexity. To create something from nothing means to make a system that seeks to some kind of self-order and works. We define the main organizational principles of complex systems and present techniques for their implementation. The techniques are applied to a specific case.
Keywords: Complexity; Evolutional systems; Simulations; Political sciences; Education